Poly(ADP-ribose) polymerases covalently modify strand break termini in DNA fragments in vitro - Talhaoui I. (2016)
Fondation ARC (http://www.arc-cancer.net) [PJA20151203415 to A.A.I.]; ERA.Net RUS Plus (www.eranet-rus.eu) [#306 to A.A.I. and RFBR-16-54-76010 to O.I.L.]; Electricité de France (http://www.edf.fr) [RB 2016-17 to M.K.S.]; Science Committee of the Ministry of Education and Science of the Republic of Kazakhstan (program 0212/PTF-14-OT) [3755/GF4 and 2835/GF3] (http://www.nu.edu.kz) to B.T.M.; RSF [14-24-00038 to O.I.L.]; RFBR [15-54-16003]; Program of RAS on Molecular and Cellular Biology [6.4]; postdoctoral and doctoral fellowships from Fondation ARC (http://www.arc-cancer.net) [PDF20110603195 to I.T. and G.Z.] and CIENCIACTIVA/CONCYTEC (www.cienciactiva.gob.pe), respectively. Funding for open access charge: National Laboratory Astana, Nazarbayev University, Astana, Republic of Kazakhstan.